Composition for preparing autoclaved brick, autoclaved brick and preparation method of autoclaved brick
By using compositions of coal gasification slag, softened sludge, fly ash and cement to prepare autoclaved bricks, the problems of complex processes, low resource utilization and high cost in the prior art are solved, and efficient and low-cost resource utilization and improvement of compressive strength are achieved.
Patent Information
- Application Number
- CN202411696598.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-03-25
AI Technical Summary
In the prior art, the process of preparing autoclaved bricks using coal gasification slag or fly ash as raw materials is complex, the resource utilization rate is low and the cost is high, and alkali cracking is prone to occur.
A composition for preparing autoclaved bricks is provided, including coal gasification slag, softened sludge, fly ash and cement. The total content of coal gasification slag, softened sludge and fly ash in the composition is ≥90 wt%, and the autoclaved bricks are prepared by ball milling treatment, stirring, pressing molding and autoclaving treatment.
The resource utilization rate of various solid wastes is improved, production costs are reduced, alkali cracking is avoided, and the compressive strength of the autoclaved brick is improved.
Smart Images

Figure CN119683911A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of solid waste resource utilization, and in particular to a composition for preparing autoclaved bricks, autoclaved bricks and a preparation method thereof. Background Art
[0002] Coal gasification is one of the core technologies for clean and efficient utilization of coal. It refers to the process of converting coal into synthesis gas and a small amount of residue by chemical reaction between coal and gasifying agent. In the process of incomplete combustion of coal and oxygen or oxygen-enriched air to produce CO and H2, inorganic minerals in coal undergo different physical and chemical transformations and form solid residues along with residual carbon particles in coal. The solid residues can be divided into coarse residues and fine residues. The coarse residues are discharged from the slag outlet at the bottom of the gasifier. In the process of coal gasification, the black water at the bottom of the quenching chamber, separator and water washing tower in the gasifier is further concentrated by low-pressure and vacuum flash evaporation, and then separated into fine residue and clarified ash water by clarification tank and ash water pool. Part of the ash water is discharged as wastewater and sent to subsequent units for treatment and recycling. In the subsequent treatment process of decalcification and suspended solids, lime, NaOH and other agents are added to soften the sludge to produce softened sludge. In order to meet the demand for superheated steam in each process stage, the high-pressure pulverized coal furnace sprays pulverized coal into the pulverized coal boiler, which burns at 1300℃~1600℃ and discharges fly ash, which is then produced after electrostatic precipitator.
[0003] At present, the process of resource utilization of coal gasification slag generally has problems such as complex technology, low utilization rate and high cost, which leads to high investment of enterprises, great environmental pressure but low returns. For the disposal of softened sludge, there are usually problems such as difficult operation and maintenance of sludge dewatering machines, high consumption of reagents and limited transportation of sludge. At present, the building materials produced with fly ash as raw materials mainly include hollow blocks, autoclaved bricks, sintered bricks and other building materials products. The technology is relatively mature and the country has relevant technical standards. At present, there are no relevant technical reports on the coordinated use of coal gasification slag, softened sludge and fly ash to prepare autoclaved bricks.
[0004] The existing document (publication number CN106278105A) discloses an autoclaved fly ash brick and a method for making the same. The autoclaved fly ash brick includes the following raw materials: coal gasification furnace slag, fly ash, aggregate, carbide slag, and phosphogypsum. The fly ash content in the above formula is low, and a certain amount of coal gasification furnace slag is added at the same time, which not only improves the production environment with a large amount of dust due to the high fly ash content, increases the utilization of coal gasification furnace slag, reduces production costs, and improves the performance indicators of the autoclaved fly ash brick product. The appearance color of the product is similar to that of antique blue bricks. However, commercial active raw materials such as phosphogypsum are added during the production process of the above autoclaved fly ash brick to ensure that the working performance of the product can meet the application requirements, but this also indirectly increases the cost of resource utilization and the complexity of the process. At the same time, the addition of commercial active raw materials will make it difficult to control the amount of each component, thereby causing the product to have alkali reversion cracking and other phenomena.
[0005] In summary, researching and developing an autoclaved brick with high solid waste utilization rate, low production cost, simple preparation process and high compressive strength is of great significance for the resource utilization of coal gasification slag, softened sludge and fly ash. Summary of the invention
[0006] The main purpose of the present invention is to provide a composition for preparing autoclaved bricks, autoclaved bricks and a preparation method thereof, so as to solve the problems in the prior art of preparing autoclaved bricks using coal gasification slag or fly ash as raw materials, such as complex preparation process, low resource utilization rate and high cost, and easy occurrence of alkali reversion cracking.
[0007] In order to achieve the above-mentioned object, the present invention provides a composition for preparing autoclaved bricks, which comprises: coal gasification slag, softened sludge, fly ash and cement, wherein the total content of coal gasification slag, softened sludge and fly ash is ≥90wt% based on the weight percentage of the composition.
[0008] Furthermore, the weight ratio of the sum of the weight of coal gasification slag, softened sludge and fly ash to cement is (90-95):(5-10); preferably, based on the weight percentage of the composition, the content of coal gasification slag is 25-40wt%, the content of softened sludge is 20-30wt%, the content of fly ash is 35-45wt%, and the content of cement is 5-10wt%.
[0009] Furthermore, the coal gasification slag includes calcium oxide, aluminum oxide, magnesium oxide and silicon dioxide; preferably, calculated as a percentage by weight of the coal gasification slag, the content of calcium oxide in the coal gasification slag is ≥10wt%, the content of aluminum oxide is ≥20wt%, the content of magnesium oxide is ≤5wt%, and the content of silicon dioxide is ≥45wt%; preferably, calculated as a percentage by weight of the coal gasification slag, the content of calcium oxide in the coal gasification slag is 10-20wt%, the content of aluminum oxide is 20-30wt%, the content of magnesium oxide is 1-5wt%, and the content of silicon dioxide is 45-60wt%.
[0010] Furthermore, the softened sludge includes calcium oxide, magnesium oxide and silicon dioxide; preferably, based on the weight percentage of the softened sludge, the content of calcium oxide in the softened sludge is ≥60wt%, the content of magnesium oxide is ≤15wt%, and the content of silicon dioxide is ≥10wt%; preferably, based on the weight percentage of the softened sludge, the content of calcium oxide in the softened sludge is 60-75wt%, the content of magnesium oxide is 1-15wt%, and the content of silicon dioxide is 10-20wt%.
[0011] Furthermore, the fly ash includes calcium oxide, aluminum oxide and silicon dioxide; preferably, the content of calcium oxide in the fly ash is 5-15wt%, the content of aluminum oxide is 20-30wt%, and the content of silicon dioxide is 45-55wt%, calculated as a percentage by weight of the fly ash.
[0012] Furthermore, the composition also includes an auxiliary agent; preferably, the auxiliary agent is selected from potassium oxalate and / or a mixture of polyvinyl alcohol and calcium hydroxide; preferably, the content of the auxiliary agent is 3-10wt% based on the total weight of coal gasification slag, softened sludge, fly ash and cement; preferably, the auxiliary agent is potassium oxalate, and the weight percentage of potassium oxalate is 2-8wt%, or, the auxiliary agent is a mixture of polyvinyl alcohol and calcium hydroxide, and the weight percentage of the mixture of polyvinyl alcohol and calcium hydroxide is 5-10wt%, or, the auxiliary agent is a combination of potassium oxalate and a mixture of polyvinyl alcohol and calcium hydroxide, and the weight ratio of the two is (3-8):(4-7); more preferably, the weight ratio of polyvinyl alcohol to calcium hydroxide in the mixture of polyvinyl alcohol and calcium hydroxide is (5-8):(15-24).
[0013] The second aspect of the present application also provides a method for preparing an autoclaved brick, which is prepared using the composition for preparing an autoclaved brick provided in the present application. The method for preparing an autoclaved brick comprises: step S1, ball milling coal gasification slag, softened sludge, fly ash and cement to obtain a mixture; step S2, mixing the mixture with water to obtain a mixed slurry; step S3, pressing and molding the mixed slurry to obtain a brick blank; step S4, autoclaving the brick blank to obtain an autoclaved brick.
[0014] Furthermore, the weight ratio of the total weight of the softened sludge and fly ash to water is 100:(15-20).
[0015] Furthermore, in step S1, the ball milling treatment is performed at a temperature of 25 to 35°C, a rotation speed of 200 to 300 rpm, and a time of 5 to 10 min.
[0016] Furthermore, in step S2, the mixing temperature is 30-35°C and the mixing time is 10-20 min; preferably, the mixing process is a stirring process, and the stirring rate is preferably 200-250 rpm.
[0017] Furthermore, in step S3, the pressure of the pressing molding is 15 to 25 MPa, and the time is 30 to 90 seconds.
[0018] Further, in step S4, the autoclave treatment includes a heating stage, a heat preservation stage and a cooling stage in sequence, wherein the temperature of the heat preservation stage is 190-220°C, the time is 5-8h, and the steam pressure is 0.8-1.5MPa; preferably, during the autoclave treatment, the heating rate of the heating stage is 45-55°C / h, and the time is 3-4h; preferably, during the autoclave treatment, the cooling rate of the cooling stage is 45-55°C / h, and the time is 3-4h.
[0019] Furthermore, before step S1, the preparation method of the autoclaved brick also includes: performing a first drying treatment on the undried coal gasification slag, preferably obtaining the coal gasification slag after screening treatment; and / or performing a second drying treatment on the undried softened sludge to obtain softened sludge; preferably, the temperature of the first drying treatment is 40-60°C, and the time is 3-5h; preferably, the weight percentage of water in the coal gasification slag is ≤10wt%; preferably, the temperature of the second drying treatment is 100-110°C, and the time is 12-18h; preferably, the weight percentage of water in the softened sludge is ≤5wt%; preferably, the average particle size of the coal gasification slag is 50-200μm; preferably, the sieve residue after screening treatment is ≤5wt% in terms of the weight percentage of the coal gasification slag.
[0020] The third aspect of the present application also provides an autoclaved brick, which is prepared by the above-mentioned method for preparing autoclaved bricks provided in the present application.
[0021] By applying the technical solution of the present invention, the composition for preparing autoclaved bricks in the present application includes coal gasification slag, softened sludge, fly ash and cement. Compared with the autoclaved bricks in the prior art that add commercial active raw materials such as gypsum, slaked lime, sand, and clay, the present application can improve the resource utilization rate of various solid wastes and reduce costs. At the same time, since no commercial active components are added, the addition amount of each component in the composition in the present application is easy to control, and the occurrence of product alkali back cracking can be suppressed. The main components of coal gasification slag include mineral crystals of quartz and cristobalite, which can participate in the hydration reaction as a siliceous material. The softened sludge is mainly composed of calcium carbonate mineral phase, which contains a small amount of tricalcium silicate (abbreviated as C3S) and dicalcium silicate (abbreviated as C2S) that can generate calcium hydroxide during the hydration reaction, can increase the alkalinity of the liquid phase, and can be used as an alkali-activated raw material. Fly ash has potential volcanic ash activity and can improve the fluidity of the slurry. Softened sludge can be used as a gel material. The calcium carbonate mineral phase it contains can promote the dissolution of silicate in cement, so that after hydration, it provides nucleation sites for the hydration products of coal gasification slag, softened sludge and fly ash, forming active calcium-based products of colloidal hydrated calcium silicate. At the same time, softened sludge, as an alkali-activated raw material, can react with coal gasification slag and fly ash to obtain stable CSH (CaO·SiO2·H2O) gel and CASH (CaO·Al2O3·SiO2·H2O) gel, thereby improving the utilization rate of coal gasification slag and fly ash, and can form tobermorite crystals and xonotlite crystals, thereby improving the compressive strength of autoclaved bricks. Coal gasification sludge can be used as fine aggregate to connect and fill with other gel materials inside the autoclaved brick body, thereby improving the compressive strength of the autoclaved brick.
[0022] The sum of the contents of coal gasification slag, softened sludge and fly ash includes but is not limited to the above range. Limiting it within the above range can improve the compressive strength of the autoclaved bricks, while also improving the resource utilization rate of various solid wastes and reducing costs. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:
[0024] Figure 1 The scanning electron microscope image (SEM image, magnification 5000 times) of the autoclaved brick prepared in Example 1 of the present application is shown;
[0025] Figure 2 The scanning electron microscope image (SEM image, magnification of 10000 times) of the autoclaved brick prepared in Example 1 of the present application is shown;
[0026] Figure 3The scanning electron microscope image (SEM image, magnification of 10000 times) of the autoclaved brick prepared in Example 1 of the present application is shown;
[0027] Figure 4 The appearance photo of the autoclaved brick prepared in Example 1 of the present application is shown;
[0028] Figure 5 The scanning electron microscope image (SEM image) of the autoclaved brick prepared in Comparative Example 1 of the present application is shown;
[0029] Figure 6 The following is a photograph of the appearance of the autoclaved bricks prepared in Comparative Example 1 of the present application. DETAILED DESCRIPTION
[0030] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below in conjunction with the embodiments.
[0031] As described in the background technology, the existing autoclaved bricks prepared with coal gasification slag or fly ash as raw materials have the problems of complex preparation process, low resource utilization rate and high cost, and the autoclaved bricks are prone to alkali reversion and cracking. In order to solve the above technical problems, the first aspect of the present application provides a composition for preparing autoclaved bricks, the composition comprising: coal gasification slag, softened sludge, fly ash and cement, wherein the total content of coal gasification slag, softened sludge and fly ash is ≥90wt% in terms of weight percentage of the composition.
[0032] The composition used for preparing autoclaved bricks in the present application includes coal gasification slag, softened sludge, fly ash and cement. Compared with the autoclaved bricks in the prior art that add commercial active raw materials such as gypsum, slaked lime, sand, and clay, the present application can improve the resource utilization rate of various solid wastes and reduce costs. At the same time, since no commercial active components are added, the addition amount of each component in the composition in the present application is easy to control, and the occurrence of product alkali back cracking can be suppressed. The main components of coal gasification slag include mineral crystals of quartz and cristobalite, which can participate in the hydration reaction as a siliceous material. The softened sludge is mainly composed of calcium carbonate mineral phase, which contains a small amount of tricalcium silicate (abbreviated as C3S) and dicalcium silicate (abbreviated as C2S) that can generate calcium hydroxide during the hydration reaction, can increase the alkalinity of the liquid phase, and can be used as an alkali-activated raw material. Fly ash has potential volcanic ash activity and can improve the fluidity of the slurry. Softened sludge can be used as a gel material. The calcium carbonate mineral phase it contains can promote the dissolution of silicate in cement, so that after hydration, it provides nucleation sites for the hydration products of coal gasification slag, softened sludge and fly ash, forming CSH (CaO·SiO2·H2O) gel, an active calcium-based product of colloidal calcium silicate hydrate. At the same time, softened sludge can be used as an alkali-activated raw material to react with coal gasification slag and fly ash to obtain stable CSH gel and CASH (CaO·Al2O3·SiO2·H2O) gel, thereby improving the utilization rate of coal gasification slag and fly ash, and can form tobermorite crystals and xonotlite crystals, thereby improving the compressive strength of autoclaved bricks. Coal gasification sludge can be used as fine aggregate to connect and fill with other gel materials inside the autoclaved brick body, thereby improving the compressive strength of the autoclaved brick.
[0033] The sum of the contents of coal gasification slag, softened sludge and fly ash includes but is not limited to the above range. Limiting it within the above range can improve the compressive strength of the autoclaved bricks, while also improving the resource utilization rate of various solid wastes and reducing costs.
[0034] In a preferred embodiment, the weight ratio of the sum of the weights of coal gasification slag, softened sludge and fly ash to cement is (90-95):(5-10). The weight ratio of the sum of the weights of coal gasification slag, softened sludge and fly ash to cement includes but is not limited to the above range. Limiting it within the above range is conducive to further promoting the dissolution of silicates in cement, and is conducive to providing more nucleation sites for the hydration products of coal gasification slag, softened sludge and fly ash after the hydration reaction. At the same time, it is conducive to improving the synergistic effect of coal gasification slag, softened sludge and fly ash in the hydration reaction, and is conducive to obtaining more stable CSH gel and CASH gel, thereby facilitating the formation of needle-shaped tobermorite and plate-shaped xonotlite crystals, and further facilitating the improvement of the compressive strength of autoclaved bricks. In addition, it is also conducive to improving the resource utilization rate of various solid wastes, reducing costs, and inhibiting the occurrence of product alkali back cracking.
[0035] In order to further promote the dissolution of silicate in cement, and further provide more nucleation sites for the hydration products of coal gasification slag, softened sludge and fly ash after hydration, so as to further obtain more stable CSH gel and CASH gel, and further improve the compressive strength of autoclaved bricks, and at the same time, in order to further improve the resource utilization rate of various solid wastes and further reduce costs, preferably, based on the weight percentage of the composition, the content of coal gasification slag is 25-40wt%, the content of softened sludge is 20-30wt%, the content of fly ash is 35-45wt%, and the content of cement is 5-10wt%.
[0036] In a preferred embodiment, the coal gasification slag includes calcium oxide, aluminum oxide, magnesium oxide and silicon dioxide; in terms of weight percentage of the coal gasification slag, the content of calcium oxide in the coal gasification slag is ≥10wt%, the content of aluminum oxide is ≥20wt%, the content of magnesium oxide is ≤5wt%, and the content of silicon dioxide is ≥45wt%. The contents of calcium oxide, aluminum oxide, magnesium oxide and silicon dioxide in the coal gasification slag include but are not limited to the above ranges, and limiting them within the above ranges is conducive to the participation of siliceous materials in the coal gasification slag in the hydration reaction, is conducive to improving the reaction efficiency of the hydration reaction, is conducive to obtaining stable CSH gel and CASH gel, and thus is conducive to improving the compressive strength of the autoclaved brick; and is also conducive to inhibiting the occurrence of product alkali back cracking.
[0037] In order to further improve the reaction efficiency of the hydration reaction, further improve the yield of CSH gel and CASH gel, thereby further improving the compressive strength of the autoclaved brick, and further inhibit the occurrence of alkali cracking of the product, preferably, the content of calcium oxide in the gasification slag is 10-20wt%, the content of aluminum oxide is 20-30wt%, the content of magnesium oxide is 1-5wt%, and the content of silicon dioxide is 45-60wt%, calculated as a percentage by weight of the coal gasification slag.
[0038] In a preferred embodiment, the softened sludge includes calcium oxide, magnesium oxide and silicon dioxide. In terms of weight percentage of the softened sludge, the content of calcium oxide in the softened sludge is ≥60wt%, the content of magnesium oxide is ≤15wt%, and the content of silicon dioxide is ≥10wt%. The contents of calcium oxide, magnesium oxide and silicon dioxide in the softened sludge include but are not limited to the above ranges. Limiting them within the above ranges is conducive to the softened sludge participating in the hydration reaction as a calcareous material, improving the alkalinity of the liquid phase, improving the reaction efficiency of the hydration reaction, and obtaining stable CSH gel and CASH gel, thereby improving the compressive strength of the autoclaved brick; and it is also conducive to inhibiting the occurrence of product alkali back cracking.
[0039] In order to further improve the alkalinity of the liquid phase, further improve the reaction efficiency of the hydration reaction, further improve the yield of CSH gel and CASH gel, thereby further improving the compressive strength of the autoclaved brick, and further inhibit the occurrence of product alkali cracking, preferably, the content of calcium oxide in the softened sludge is 60-75wt%, the content of magnesium oxide is 1-15wt%, and the content of silicon dioxide is 10-20wt%, calculated as a percentage by weight of the softened sludge.
[0040] In a preferred embodiment, the fly ash includes calcium oxide, aluminum oxide and silicon dioxide; in terms of weight percentage of the fly ash, the content of calcium oxide in the fly ash is 5-15wt%, the content of aluminum oxide is 20-30wt%, and the content of silicon dioxide is 45-55wt%. The contents of calcium oxide, aluminum oxide and silicon dioxide in the fly ash include but are not limited to the above ranges, and limiting them within the above ranges is beneficial to improving the reaction efficiency of the hydration reaction, and is beneficial to obtaining stable CSH gel and CASH gel, thereby improving the compressive strength of the autoclaved brick; and it is also beneficial to inhibiting the occurrence of product alkali back cracking.
[0041] In a preferred embodiment, the composition further includes an auxiliary agent, which includes but is not limited to a mixture of potassium oxalate and / or polyvinyl alcohol (PVA) and calcium hydroxide. The introduction of potassium oxalate is conducive to its formation of a stable complex with metal ions (such as calcium ions and aluminum ions) in coal gasification slag and fly ash, which is conducive to improving the activity of metal ions, thereby helping to improve the reaction efficiency of the hydration reaction and the yield of the hydration product; the introduction of the mixture of PVA and calcium hydroxide, on the one hand, PVA has a reinforcing effect, which is conducive to improving the mechanical properties of the autoclaved brick, on the other hand, calcium hydroxide is conducive to increasing the concentration of alkali in the liquid phase, thereby helping to improve the reaction efficiency of the hydration reaction, and the simultaneous introduction of the two can exert their synergistic effect, thereby helping to improve the compressive strength of the autoclaved brick.
[0042] In order to further improve the reaction efficiency of the hydration reaction, further improve the yield of the hydration product, and further improve the compressive strength of the autoclaved brick, preferably, the content of the additive is 3-10wt% as a percentage of the total weight of the coal gasification slag, softened sludge, fly ash and cement.
[0043] In order to further improve the reaction efficiency of the hydration reaction, further improve the yield of the hydration product, and further improve the compressive strength of the autoclaved brick, preferably, the auxiliary agent is potassium oxalate, and the weight percentage of potassium oxalate is 2-8wt%, or, the auxiliary agent is a mixture of polyvinyl alcohol and calcium hydroxide, and the weight percentage of the mixture of polyvinyl alcohol and calcium hydroxide is 5-10wt%, or, the auxiliary agent is a combination of potassium oxalate and a mixture of polyvinyl alcohol and calcium hydroxide, and the weight ratio of the two is (3-8):(4-7).
[0044] In order to better exert the synergistic effect of PVA and calcium hydroxide, thereby further improving the reaction efficiency of the hydration reaction and further improving the compressive strength of the autoclaved brick, preferably, the weight ratio of polyvinyl alcohol to calcium hydroxide in the mixture of polyvinyl alcohol and calcium hydroxide is (5-8):(15-24).
[0045] The second aspect of the present application also provides a method for preparing an autoclaved brick, which is prepared using the above-mentioned composition for preparing an autoclaved brick, and the preparation method comprises: step S1, ball milling coal gasification slag, softened sludge, fly ash and cement to obtain a mixture; step S2, mixing the mixture with water to obtain a mixed slurry; step S3, pressing and molding the mixed slurry to obtain a brick blank; step S4, autoclaving the brick blank to obtain an autoclaved brick.
[0046] In the preparation method of the above-mentioned autoclaved bricks provided in the present application, the ball milling treatment of the coal gasification slag, softened sludge, fly ash and cement in step S1 can improve the dispersion uniformity of each component, reduce the particle size of the mixture, reduce the porosity of the mixture, thereby reducing the porosity of the autoclaved brick and improving its density. At the same time, it can also increase the specific surface area of the mixture, thereby improving the reaction efficiency of the subsequent hydration reaction, increasing the yield of CSH gel and CASH gel, and then improving the compressive strength of the autoclaved brick; wherein the main components of the coal gasification slag include mineral crystals of quartz and cristobalite, which can participate in the hydration reaction as a siliceous material, the softened sludge is mainly composed of calcium carbonate mineral phase, which contains a small amount of C3S and C2S, which can generate calcium hydroxide during the hydration reaction, can increase the alkalinity of the liquid phase, and can be used as an alkali-activated raw material, and the fly ash has potential volcanic ash activity and can improve the fluidity of the slurry. In step S2, the mixture is first mixed with water to obtain a mixed slurry. The introduction of water is conducive to promoting the occurrence of hydration reaction. The softened sludge in the mixture can be used as a gel material. The calcium carbonate mineral phase contained in the mixture can promote the dissolution of silicates in cement, so that after hydration, it provides nucleation sites for the hydration products of coal gasification slag, softened sludge and fly ash, forming a colloidal calcium-based product CSH gel of hydrated calcium silicate. At the same time, the softened sludge can be used as an alkali-activated raw material to react with coal gasification slag and fly ash to obtain stable CSH gel and CASH gel. After hardening, needle-shaped tobermorite and plate-shaped xonotlite crystals can be formed, thereby improving the compressive strength of the autoclaved brick. In step S3, the mixed slurry is pressed and formed to obtain a brick blank. Pressing and forming can improve the density of the autoclaved brick, which is convenient for subsequent autoclaving and curing. The autoclaving of the brick blank in step S4 can improve the reaction efficiency of the hydration reaction, accelerate the hardening process of the brick blank, improve the density of the autoclaved brick, and thus improve the compressive strength of the autoclaved brick. The hydration reaction of the coal gasification slag, softened sludge and fly ash in this application includes the following specific processes:
[0047] (1)Ca(OH)2+SiO2+H2O→CaO·SiO2·H2O;
[0048] (2)Ca(OH)2+Al2O3+H2O→CaO·Al2O3·H2O;
[0049] (3)Ca(OH)2+SiO2+Al2O3+H2O→CaO·Al2O3·SiO2·H2O.
[0050] In summary, compared with the prior art that uses commercial active materials such as gypsum, slaked lime, sand, and clay as raw materials when preparing autoclaved bricks, the preparation method of the above-mentioned autoclaved bricks provided in the present application is simple to operate, can improve the resource utilization rate of various solid wastes, and reduce costs. At the same time, since no commercial active components are added, the addition amount of each component in the raw material is easy to control, which can inhibit the occurrence of product alkali cracking.
[0051] In a preferred embodiment, the weight ratio of the total weight of softened sludge and fly ash to water is 100:(15-20). The weight ratio of the total weight of softened sludge and fly ash to water includes but is not limited to the above range. Limiting it within the above range is beneficial to improving the reaction efficiency of the hydration reaction, facilitating the subsequent pressing and forming to obtain brick blanks, and is beneficial to improving the density of autoclaved bricks, thereby improving the compressive strength of autoclaved bricks.
[0052] In a preferred embodiment, the temperature of the ball milling treatment in step S1 is 25-35°C, the rotation speed is 200-300rpm, and the time is 5-10min. The temperature, rotation speed and time of the ball milling treatment include but are not limited to the above ranges. Limiting them within the above ranges is conducive to improving the ball milling efficiency, improving the dispersion uniformity of each component, and reducing the particle size and porosity of the mixture, thereby improving the density of the autoclaved brick, and at the same time, it is also conducive to increasing the specific surface area of the mixture, thereby improving the reaction efficiency of the subsequent hydration reaction, and then It is beneficial to improve the compressive strength of the autoclaved brick.
[0053] In order to further improve the reaction efficiency of the subsequent hydration reaction, preferably, the average particle size of the mixture is 5 to 20 μm.
[0054] In a preferred embodiment, the mixing temperature in step S2 is 30-35° C. and the mixing time is 10-20 min. The mixing temperature and time in step S2 include but are not limited to the above ranges, and limiting them within the above ranges is conducive to improving the dispersion uniformity of the mixture in water, thereby facilitating improving the reaction efficiency of the subsequent hydration reaction.
[0055] In order to further improve the dispersion uniformity of the mixture in water, thereby further improving the reaction efficiency of the hydration reaction, preferably, the mixing process is a stirring process, and the stirring rate is preferably 200-250 rpm.
[0056] In a preferred embodiment, the pressure of the press molding in step S3 is 15-25 MPa, and the time is 30-90 seconds. The pressure and time of the press molding include but are not limited to the above ranges. Limiting them within the above ranges is conducive to improving the efficiency of the press molding, obtaining the bricks, facilitating the subsequent autoclave treatment, and also conducive to improving the production efficiency, thereby helping to reduce costs.
[0057] In a preferred embodiment, the autoclave treatment in step S4 includes a heating stage, a heat preservation stage and a cooling stage in sequence, wherein the temperature of the heat preservation stage is 190-220°C, the time is 5-8h, and the steam pressure is 0.8-1.5MPa. The temperature, time and steam pressure of the heat preservation stage include but are not limited to the above ranges, and limiting them within the above ranges is conducive to improving the reaction efficiency of the hydration reaction, accelerating the hardening process of the brick blank, thereby improving the density of the autoclaved brick, and further improving its compressive strength.
[0058] In order to further improve the reaction efficiency of the hydration reaction, to remove moisture from the bricks and inhibit cracks caused by uneven heating due to rapid heating, preferably, during the autoclave treatment, the heating rate in the heating stage is 45-55°C / h and the time is 3-4h.
[0059] In order to improve the heating uniformity of the autoclaved bricks in the cooling stage and suppress the decrease in their compressive strength, preferably, during the autoclaving process, the cooling rate in the cooling stage is 45-55°C / h and the time is 3-4h.
[0060] In a preferred embodiment, before step S1, the preparation method of the autoclaved brick further includes: performing a first drying treatment on the undried coal gasification slag, preferably obtaining the coal gasification slag after screening treatment; and / or performing a second drying treatment on the undried softened sludge to obtain softened sludge. Drying the undried coal gasification slag and the undried softened sludge separately is beneficial to reducing their moisture content and viscosity, thereby improving the dispersion uniformity in the subsequent mixing process, improving its machinability, reducing the difficulty of ball milling treatment, and also improving the efficiency of pressing and molding, and improving the density of the autoclaved brick, thereby improving the compressive strength of the autoclaved brick.
[0061] In order to facilitate the ball milling treatment and improve the efficiency of the ball milling treatment, in a preferred embodiment, the softened sludge after the second drying treatment can be directly subjected to the ball milling treatment, or can be subjected to the ball milling treatment after simple crushing.
[0062] In order to further reduce the moisture content in the coal gasification slag, further improve its workability, and further reduce the difficulty of ball milling, preferably, the temperature of the first drying treatment is 40-60° C. and the time is 3-5 hours.
[0063] In order to further improve the dispersion uniformity of the coal gasification slag in the subsequent mixing process, further improve its processability, further reduce the difficulty of ball milling, further improve the efficiency of pressing and the density of autoclaved bricks, thereby further improving the compressive strength of autoclaved bricks, preferably, the weight percentage of water in the coal gasification slag is ≤10wt%.
[0064] In a preferred embodiment, the temperature of the second drying treatment is 100-110°C and the time is 12-18 hours. The temperature and time of the second drying treatment include but are not limited to the above ranges, and limiting them within the above ranges is conducive to reducing the moisture content in the softened sludge, improving its processability, and reducing the difficulty of ball milling, thereby improving the efficiency of pressing and the density of the autoclaved bricks.
[0065] In order to further improve the dispersion uniformity of the softened sludge in the subsequent mixing process, further improve its processability, further reduce the difficulty of ball milling, further improve the efficiency of pressing and the density of autoclaved bricks, thereby further improving the compressive strength of autoclaved bricks, preferably, the weight percentage of water in the softened sludge is ≤5wt%.
[0066] In order to increase the specific surface area of the coal gasification slag and further improve its dispersion uniformity in the subsequent mixing process, thereby further improving the reaction efficiency of the hydration reaction and further improving the compressive strength of the autoclaved brick, preferably, the average particle size of the coal gasification slag is 50 to 200 μm.
[0067] In a preferred embodiment, the average particle size of the fly ash is 30 to 80 nm. The average particle size of the fly ash includes but is not limited to the above range. Limiting it within the above range is conducive to increasing the specific surface area of the fly ash and improving its dispersion uniformity in the subsequent mixing process, thereby facilitating the reaction efficiency of the hydration reaction, and further facilitating the compressive strength of the autoclaved brick.
[0068] In order to improve the utilization rate of coal gasification slag and reduce costs, preferably, the screen residue after screening is ≤5wt% in terms of weight percentage of coal gasification slag. Screen residue refers to the proportion of coal gasification slag that does not meet the average particle size range of coal gasification slag (50-200μm).
[0069] The third aspect of the present application also provides an autoclaved brick, which is prepared by the preparation method of the autoclaved brick described above in the present application.
[0070] The autoclaved bricks prepared by the above-mentioned preparation method of the present application have high compressive strength and high resource utilization rate of various solid wastes, which can reduce costs. At the same time, since no commercial active components are added to the raw materials, the addition amount of each component in the raw material composition is easy to control, which can inhibit the occurrence of product alkali cracking.
[0071] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.
[0072] The contents of the various components in the coal gasification slag, softened sludge and fly ash used in all the embodiments and comparative examples of the present application are shown in Table 1.
[0073] Table 1
[0074] Calcium oxide (wt%) Alumina (wt%) Magnesium oxide (wt%) Silicon dioxide (wt%) Coal gasification slag 10.1 23.4 2.91 47.3 Softening sludge 65.5 / 10.6 16.9 Fly ash 5.2 22.8 / 53.2
[0075] Example 1
[0076] A method for preparing autoclaved bricks is as follows:
[0077] (1) Drying the undried coal gasification slag at 40° C. for 3 h until its water content is 8 wt %, and then sieving it to obtain coal gasification slag with an average particle size of 150 μm and a sieve residue of 4 wt % after sieving; Drying the undried softened sludge at 105° C. for 15 h to obtain softened sludge with a water content of 3 wt %;
[0078] (2) Weigh 40 g of coal gasification slag, 20 g of softened sludge, 35 g of fly ash, 5 g of cement, 3 g of potassium oxalate and 5 g of a mixture of PVA and calcium hydroxide (the weight ratio of PVA to calcium hydroxide is 1:3, and the CAS number of PVA is 9002-89-5), place the above components in a planetary ball mill (Hunan Laishida Instrument Equipment Co., Ltd., LPB-6L), and ball mill for 5 min at 28° C. and 220 rpm to obtain a mixture with an average particle size of 20 μm;
[0079] (3) transferring the entire mixture prepared above into a vertical mixer, adding water, and stirring at 33° C. and 210 rpm for 10 min to obtain a mixed slurry; wherein the weight of the added water accounts for 15 wt% of the total weight of the softened sludge and fly ash;
[0080] (4) Transfer all the mixed slurry prepared above to a hydraulic brick press (Shandong Jianli Testing Technology Co., Ltd., WE-600B), and press at a pressure of 15 MPa for 30 seconds to obtain a brick;
[0081] (5) placing all the bricks prepared as described above into an autoclave for autoclaving to obtain autoclaved bricks; wherein, the temperature is increased at a heating rate of 55°C / h for 3h, and after constant temperature treatment at 190°C and 0.8MPa for 5h, the temperature is reduced at a cooling rate of 55°C / h for 3h.
[0082] The scanning electron microscope image of the autoclaved brick obtained in Example 1 is as follows Figure 1 , Figure 2 and Figure 3 As shown. Figure 1 It can be seen that the surface of the autoclaved bricks prepared in Example 1 has rhombic orthorhombic calcium carbonate crystals, and its surface is covered with a large number of flocculent structures. Figure 2 and Figure 3 It can be seen that the CSH gel and CASH gel generated by the hydration reaction formed plate-like xonotlite crystals and needle-like tobermorite crystals after hardening.
[0083] The appearance of the autoclaved bricks obtained in Example 1 is shown in the following figure: Figure 4 As shown. Figure 4 It can be seen that the autoclaved bricks prepared in Example 1 are in good appearance without any cracks.
[0084] Example 2
[0085] (1) The same as step (1) in Example 1;
[0086] (2) Weigh 35 g of coal gasification slag, 20 g of softened sludge, 35 g of fly ash, 10 g of cement, 3 g of potassium oxalate and 6 g of a mixture of PVA and calcium hydroxide (the weight ratio of PVA to calcium hydroxide is 1:3, and the CAS number of PVA is 9002-89-5), place the above components in a planetary ball mill (same as in Example 1), and ball mill for 5 min at 30° C. and 240 rpm to obtain a mixture with an average particle size of 10 μm;
[0087] (3) transferring the entire mixture prepared above into a vertical mixer, adding water, and stirring at 35° C. and 230 rpm for 10 min to obtain a mixed slurry; wherein the weight of the added water accounts for 18 wt% of the total weight of the softened sludge and fly ash;
[0088] (4) transferring all the mixed slurry prepared above to a hydraulic brick press (same as in Example 1), and pressing at a pressure of 18 MPa for 36 seconds to obtain a brick;
[0089] (5) placing all the bricks prepared as described above into an autoclave for autoclaving to obtain autoclaved bricks; wherein, the temperature is increased at a heating rate of 50°C / h for 3.5h, and after being kept at a constant temperature at 200°C and 1.0MPa for 6h, the temperature is reduced at a cooling rate of 50°C / h for 3.5h.
[0090] Example 3
[0091] (1) The same as step (1) in Example 1;
[0092] (2) Weigh 25 g of coal gasification slag, 22 g of softened sludge, 45 g of fly ash, 8 g of cement, 4 g of potassium oxalate and 6 g of a mixture of PVA and calcium hydroxide (the weight ratio of PVA to calcium hydroxide is 1:3, and the CAS number of PVA is 9002-89-5), place the above components in a planetary ball mill (same as in Example 1), and ball mill for 5 min at 35° C. and 260 pm to obtain a mixture with an average particle size of 10 μm;
[0093] (3) transferring the entire mixture prepared above into a vertical mixer, adding water, and stirring at 35° C. and 250 rpm for 10 min to obtain a mixed slurry; wherein the weight of the added water accounts for 20 wt% of the total weight of the softened sludge and fly ash;
[0094] (4) transferring all the mixed slurry prepared above to a hydraulic brick press (same as in Example 1), and pressing at a pressure of 22 MPa for 90 seconds to obtain a brick;
[0095] (5) placing all the bricks prepared as described above into an autoclave for autoclaving to obtain autoclaved bricks; wherein, the temperature is increased at a heating rate of 46°C / h for 4 hours, and after a constant temperature treatment at 210°C and 1.2 MPa for 7 hours, the temperature is reduced at a cooling rate of 46°C / h for 4 hours.
[0096] Example 4
[0097] (1) The same as step (1) in Example 1;
[0098] (2) Weigh 35 g of coal gasification slag, 20 g of softened sludge, 35 g of fly ash, 10 g of cement, 3 g of potassium oxalate and 7 g of a mixture of PVA and calcium hydroxide (the weight ratio of PVA to calcium hydroxide is 1:3, and the CAS number of PVA is 9002-89-5), place the above components in a planetary ball mill (same as in Example 1), and ball mill for 5 min at 35° C. and 240 pm to obtain a mixture with an average particle size of 10 μm;
[0099] (3) transferring the entire mixture prepared above into a vertical mixer, adding water, and stirring at 35° C. and 240 rpm for 10 min to obtain a mixed slurry; wherein the weight of the added water accounts for 20 wt% of the total weight of the softened sludge and fly ash;
[0100] (4) transferring all the mixed slurry prepared above to a hydraulic brick press (same as in Example 1), and pressing at a pressure of 25 MPa for 42 seconds to obtain a brick;
[0101] (5) placing all the bricks prepared as described above into an autoclave for autoclaving to obtain autoclaved bricks; wherein, the temperature is increased at a heating rate of 50°C / h for 4 hours, and after constant temperature treatment at 220°C and 1.5 MPa for 8 hours, the temperature is reduced at a cooling rate of 50°C / h for 4 hours.
[0102] Example 5
[0103] The difference from Example 1 is that the amounts of the components used in step (2) are as follows: 45 g of coal gasification slag, 18 g of softened sludge, 25 g of fly ash, 12 g of cement, 9 g of potassium oxalate and 6 g of a mixture of PVA and calcium hydroxide (the weight ratio of PVA to calcium hydroxide is 1:3).
[0104] Example 6
[0105] The difference from Example 1 is that an equal amount of potassium oxalate is used to replace the combination of potassium oxalate, PVA and calcium hydroxide mixture, and the remaining steps are the same as in Example 1.
[0106] Example 7
[0107] The difference from Example 1 is that an equal amount of a mixture of PVA and calcium hydroxide is used to replace the combination of potassium oxalate and the mixture of PVA and calcium hydroxide, and the remaining steps are the same as in Example 1.
[0108] Example 8
[0109] The difference from Example 1 is that an equal amount of coal gasification slag is used to replace the combination of potassium oxalate and the mixture of PVA and calcium hydroxide, and the remaining steps are the same as in Example 1.
[0110] Example 9
[0111] The difference from Example 1 is that the components in step (2) are placed in a planetary ball mill and ball-milled for 5 min at 25° C. and 200 rpm to obtain a mixture with an average particle size of 6 μm. The remaining steps are the same as in Example 1.
[0112] Example 10
[0113] The difference from Example 1 is that the components in step (2) are placed in a planetary ball mill and ball-milled for 10 min at 35° C. and 300 rpm to obtain a mixture with an average particle size of 15 μm. The remaining steps are the same as in Example 1.
[0114] Embodiment 11
[0115] The difference from Example 1 is that the components in step (2) are placed in a planetary ball mill and ball-milled for 3 min at 20° C. and 170 rpm to obtain a mixture with an average particle size of 4 μm. The remaining steps are the same as in Example 1.
[0116] Example 12
[0117] The difference from Example 1 is that in step (3), the mixture is stirred at 30°C and 200 rpm for 10 min to obtain a mixed slurry; the mixed slurry is transferred to a hydraulic brick machine and pressed at a pressure of 15 MPa for 30 s to obtain a brick blank, and the remaining steps are the same as in Example 1.
[0118] Embodiment 13
[0119] The difference from Example 1 is that in step (3), the mixture is stirred at 35°C and 250 rpm for 20 min to obtain a mixed slurry; the mixed slurry is transferred to a hydraulic brick machine and pressed at a pressure of 25 MPa for 90 s to obtain a brick blank; the remaining steps are the same as in Example 1.
[0120] Embodiment 14
[0121] The difference from Example 1 is that in step (3), the mixture is stirred at 25°C and 170 rpm for 6 min to obtain a mixed slurry; the mixed slurry is transferred to a hydraulic brick machine and pressed at a pressure of 10 MPa for 18 s to obtain a brick blank; the remaining steps are the same as in Example 1.
[0122] Embodiment 15
[0123] The difference from Example 1 is that all the bricks obtained in step (4) are placed in an autoclave for autoclave treatment to obtain autoclaved bricks; wherein the temperature is increased at a heating rate of 49°C / h for 4 hours, and after constant temperature treatment at 220°C and 1.5 MPa for 8 hours, the temperature is cooled at a cooling rate of 49°C / h for 4 hours. The remaining steps are the same as in Example 1.
[0124] Example 16
[0125] The difference from Example 1 is that all the bricks obtained in step (4) are placed in an autoclave for autoclaving to obtain autoclaved bricks; wherein the temperature is increased at a heating rate of 103°C / h for 2h, and after constant temperature treatment at 230°C and 0.6MPa for 4h, the temperature is cooled at a cooling rate of 103°C / h for 2h, and the remaining steps are the same as in Example 1.
[0126] Comparative Example 1
[0127] The difference from Example 1 is that equal amounts of calcium oxide, magnesium oxide and silicon dioxide are used to replace the softened sludge, and the remaining steps are the same as those in Example 1.
[0128] The scanning electron microscope image of the autoclaved brick obtained in Comparative Example 1 is as follows: Figure 5 As shown, the appearance photos are as follows Figure 6 As shown. Figure 5 It can be seen that in the absence of softening sludge, calcium carbonate orthorhombic crystals cannot be generated and the strength is lost. Figure 6 It can be seen that there are a small number of irregular cracks on the surface and around the autoclaved bricks prepared in Comparative Example 1.
[0129] Comparative Example 2
[0130] The difference from Example 1 is that the sum of the contents of coal gasification slag, softened sludge and fly ash in the composition for preparing autoclaved bricks is 85wt%, cement is 15wt%, and the remaining steps are the same as Example 1.
[0131] Since the cement content in the raw materials is high and the amount of solid waste is small, the resource utilization rate is low and the cost is higher than that of Example 1.
[0132] Comparative Example 3
[0133] The difference from Example 1 is that softened sludge is not introduced in step (2), and the weight ratio of coal gasification slag and fly ash to cement is the same as the weight ratio of coal gasification slag, softened sludge, fly ash and cement in Example 1, and the remaining steps are the same as Example 1.
[0134] Comparative Example 4
[0135] The difference from Example 1 is that: coal gasification slag is not introduced in step (2), and the weight ratio of softened sludge, fly ash and cement is the same as the weight ratio of coal gasification slag, softened sludge, fly ash and cement in Example 1, and the remaining steps are the same as Example 1.
[0136] Comparative Example 5
[0137] The difference from Example 1 is that fly ash is not introduced in step (2), and the weight ratio of coal gasification slag, softened sludge and cement is the same as the weight ratio of coal gasification slag, softened sludge, fly ash and cement in Example 1, and the remaining steps are the same as Example 1.
[0138] Comparative Example 6
[0139] The difference from Example 1 is that cement is not introduced in step (2), and an equal amount of softened sludge is used instead, and the remaining steps are the same as Example 1.
[0140] The autoclaved bricks prepared in all the embodiments and comparative examples of the present application are cylindrical samples. The autoclaved bricks prepared in all the above embodiments and comparative examples are subjected to performance tests. The specific test methods are as follows: (1) the compressive strength of the autoclaved bricks is measured according to the method in Appendix B of JC / T 239-2014; (2) after the autoclaving process, the appearance of the autoclaved bricks is inspected to observe whether cracks appear. If cracks appear, the position, shape, width and length of the cracks are recorded. The shape of the cracks includes vertical straight cracks and oblique cracks at door and window openings; the width of the cracks is ≤0.5 mm; the building materials industry standard for autoclaved fly ash bricks is JC / T239-2014, and the strength grade should reach MU10.
[0141] The test results are shown in Table 2.
[0142] Table 2
[0143] Compressive strength(MPa) Appearance Example 1 15 intact Example 2 17 intact Example 3 22 intact Example 4 19 intact Example 5 13 intact Example 6 11 intact Example 7 12 intact Example 8 10 intact Example 9 16 intact Example 10 15 intact Embodiment 11 13 intact Example 12 14 intact Embodiment 13 15 intact Embodiment 14 12 intact Embodiment 15 15 intact Example 16 11 Minor cracks Comparative Example 1 13 crack Comparative Example 2 14 intact Comparative Example 3 7 intact Comparative Example 4 9 intact Comparative Example 5 8 intact Comparative Example 6 5 intact
[0144] From the above description, it can be seen that the above embodiments of the present invention achieve the following technical effects:
[0145] By comparing Example 1 and Comparative Example 1, it can be seen that compared with the autoclaved bricks in the prior art to which commercial active raw materials such as gypsum, slaked lime, sand, and clay are added, the autoclaved bricks prepared by the above-mentioned autoclaved brick preparation method provided in the present application can improve the resource utilization rate of various solid wastes and reduce costs. At the same time, since no commercial active components are added, the addition amount of each component in the composition in the present application is easy to control, thereby suppressing the phenomenon of alkali reversion and cracking of the autoclaved bricks.
[0146] By comparing Example 1 and Comparative Example 2, it can be seen that, compared with other ranges, limiting the sum of the contents of coal gasification slag, softened sludge and fly ash within the above-mentioned range of the present application can improve the compressive strength of the autoclaved bricks, while also improving the resource utilization rate of various solid wastes and reducing costs.
[0147] By comparing Example 1 with Comparative Examples 3 to 6, it can be seen that the calcium carbonate mineral phase contained in the softened sludge can promote the dissolution of silicates in cement, so that after hydration, it can provide nucleation sites for the synergistic hydration products of coal gasification slag, softened sludge and fly ash, forming an active calcium-based product CSH (CaO·SiO2·H2O) gel of colloidal calcium silicate hydrate. At the same time, the softened sludge can be used as an alkali-activated raw material to react with coal gasification slag and fly ash to obtain stable CSH gel and CASH (CaO·Al2O3·SiO2·H2O) gel, thereby improving the utilization rate of coal gasification slag and fly ash, and can form tobermorite crystals and xonotlite crystals, thereby improving the compressive strength of the autoclaved brick; the coal gasification sludge can be used as fine aggregate to connect and fill with other gel materials inside the autoclaved brick body, thereby improving the compressive strength of the autoclaved brick.
[0148] Comparing Examples 1 to 5, it can be seen that, compared with other ranges, setting the contents of coal gasification slag, softened sludge, fly ash and cement within the above range is beneficial to improving the synergistic effect of coal gasification slag, softened sludge and fly ash in the hydration reaction, and is beneficial to obtaining more stable CSH gel and CASH gel, thereby being beneficial to the formation of needle-shaped tobermorite and plate-shaped xonotlite crystals, and further beneficial to improving the compressive strength of the autoclaved bricks, and is beneficial to inhibiting the occurrence of product alkali cracking.
[0149] By comparing Examples 1 and 6 to 8, it can be seen that, compared with other types, the use of the above-mentioned types of additives in the present application is beneficial to improving the reaction efficiency of the hydration reaction, and is beneficial to increasing the yield of the hydration product, thereby helping to improve the compressive strength of the obtained autoclaved product.
[0150] By comparing Examples 1 and 9 to 11, it can be seen that the temperature, rotation speed and time of the ball milling treatment include but are not limited to the above ranges. Limiting them within the above ranges is beneficial to improving the efficiency of the ball milling treatment, improving the dispersion uniformity of each component, reducing the particle size and porosity of the mixture, thereby improving the density of the autoclaved brick, and at the same time, it is also beneficial to increase the specific surface area of the mixture, thereby improving the reaction efficiency of the subsequent hydration reaction, and further helping to improve the compressive strength of the autoclaved brick.
[0151] By comparing Examples 1 and 12 to 14, it can be seen that the pressure and time of the pressing molding include but are not limited to the above ranges. Limiting them within the above ranges is beneficial to improving the efficiency of the pressing molding, facilitating subsequent autoclaving, and obtaining an autoclaved product with higher compressive strength.
[0152] Comparing Examples 1, 15 and 16, Example 16 was heated unevenly due to its too fast heating and cooling rate and high temperature of constant temperature treatment, resulting in slight cracks. It can be seen that, compared with other ranges, limiting the process parameters of each stage in the autoclave treatment to the above range of the present application is beneficial to improving the reaction efficiency of the hydration reaction, accelerating the hardening process of the brick blank, and improving the density of the autoclaved brick. At the same time, it is also beneficial to improve the heating uniformity of the autoclaved brick, inhibit the decrease of its compressive strength, and thus improve its compressive strength.
[0153] It should be noted that the terms "first", "second", etc. in the specification and claims of the present application are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the terms used in this way can be interchangeable where appropriate, so that the embodiments of the present application described herein can be implemented in an order other than those described herein, for example.
[0154] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A composition for preparing autoclaved bricks, characterized in that: The composition for preparing autoclaved bricks comprises: coal gasification slag, softened sludge, fly ash and cement, wherein, in terms of weight percentage of the composition, the total content of the coal gasification slag, the softened sludge and the fly ash is ≥90wt%.
2. The composition for preparing autoclaved bricks according to claim 1, characterized in that: The weight ratio of the sum of the weight of the coal gasification slag, the softened sludge and the fly ash to the weight of the cement is (90-95):(5-10); Preferably, in terms of weight percentage of the composition, the content of the coal gasification slag is 25-40wt%, the content of the softened sludge is 20-30wt%, the content of the fly ash is 35-45wt%, and the content of the cement is 5-10wt%.
3. The composition for preparing autoclaved bricks according to claim 1, characterized in that: The coal gasification slag comprises calcium oxide, aluminum oxide, magnesium oxide and silicon dioxide; Preferably, in terms of weight percentage of the coal gasification slag, the content of calcium oxide in the coal gasification slag is ≥10wt%, the content of aluminum oxide is ≥20wt%, the content of magnesium oxide is ≤5wt%, and the content of silicon dioxide is ≥45wt%; Preferably, in terms of weight percentage of the coal gasification slag, the content of calcium oxide in the coal gasification slag is 10-20wt%, the content of aluminum oxide is 20-30wt%, the content of magnesium oxide is 1-5wt%, and the content of silicon dioxide is 45-60wt%; Preferably, the softening sludge comprises calcium oxide, magnesium oxide and silicon dioxide; Preferably, the content of calcium oxide in the softened sludge is ≥60wt%, the content of magnesium oxide is ≤15wt%, and the content of silicon dioxide is ≥10wt% in terms of weight percentage of the softened sludge; Preferably, the content of calcium oxide in the softened sludge is 60-75wt%, the content of magnesium oxide is 1-15wt%, and the content of silicon dioxide is 10-20wt% in terms of weight percentage of the softened sludge; Preferably, the fly ash comprises calcium oxide, aluminum oxide and silicon dioxide; Preferably, in terms of weight percentage of the fly ash, the content of calcium oxide in the fly ash is 5-15wt%, the content of aluminum oxide is 20-30wt%, and the content of silicon dioxide is 45-55wt%.
4. The composition for preparing autoclaved bricks according to any one of claims 1 to 3, characterized in that: The composition also includes an adjuvant; Preferably, the auxiliary agent is selected from potassium oxalate and / or a mixture of polyvinyl alcohol and calcium hydroxide; Preferably, the content of the auxiliary agent is 3-10wt% based on the total weight of the coal gasification slag, the softened sludge, the fly ash and the cement; Preferably, the auxiliary agent is potassium oxalate, and the weight percentage of the potassium oxalate is 2-8wt%, or the auxiliary agent is a mixture of polyvinyl alcohol and calcium hydroxide, and the weight percentage of the mixture of polyvinyl alcohol and calcium hydroxide is 5-10wt%, or the auxiliary agent is a combination of potassium oxalate and a mixture of polyvinyl alcohol and calcium hydroxide, and the weight ratio of the two is (3-8):(4-7); More preferably, the weight ratio of polyvinyl alcohol to calcium hydroxide in the mixture of polyvinyl alcohol and calcium hydroxide is (5-8):(15-24).
5. A method for preparing autoclaved bricks, characterized in that: The autoclaved brick is prepared by using the composition for preparing autoclaved brick according to any one of claims 1 to 4, and the preparation method of the autoclaved brick comprises: Step S1, ball-milling coal gasification slag, softened sludge, fly ash and cement to obtain a mixture; Step S2, mixing the mixture with water to obtain a mixed slurry; Step S3, pressing and molding the mixed slurry to obtain a brick; Step S4, autoclaving the brick blank to obtain the autoclaved brick.
6. The method for preparing autoclaved bricks according to claim 5, characterized in that: The weight ratio of the total weight of the softened sludge and the fly ash to the water is 100:(15-20).
7. The method for preparing autoclaved bricks according to claim 5, characterized in that: The ball milling treatment is performed at a temperature of 25 to 35°C, a rotation speed of 200 to 300 rpm, and a time of 5 to 10 minutes; Preferably, the mixing temperature is 30-35°C and the mixing time is 10-20 minutes; Preferably, the mixing process is a stirring process, and preferably the stirring rate is 200-250 rpm; Preferably, the compression molding pressure is 15-25 MPa and the time is 30-90 s.
8. The method for preparing autoclaved bricks according to claim 7, characterized in that: The autoclave treatment includes a heating stage, a heat preservation stage and a cooling stage in sequence, wherein the temperature of the heat preservation stage is 190-220° C., the time is 5-8 hours, and the steam pressure is 0.8-1.5 MPa; Preferably, during the autoclave treatment, the heating rate in the heating stage is 45-55°C / h and the time is 3-4h; Preferably, during the autoclave treatment, the cooling rate in the cooling stage is 45-55° C. / h and the time is 3-4 hours.
9. The method for preparing the autoclaved brick according to any one of claims 5 to 8, characterized in that: Before the step S1, the method for preparing the autoclaved brick further comprises: performing a first drying treatment on the undried coal gasification slag, preferably obtaining the coal gasification slag after screening treatment; and / or performing a second drying treatment on the undried softened sludge to obtain the softened sludge; Preferably, the temperature of the first drying treatment is 40-60°C and the time is 3-5h; Preferably, the weight percentage of water in the coal gasification slag is ≤10wt%; Preferably, the temperature of the second drying treatment is 100-110°C and the time is 12-18 hours; Preferably, the weight percentage of water in the softened sludge is ≤5wt%; Preferably, the average particle size of the coal gasification slag is 50 to 200 μm; Preferably, the residue after the screening treatment is ≤5wt% based on the weight percentage of the coal gasification slag.
10. An autoclaved brick, characterized in that: The autoclaved brick is prepared by the method for preparing autoclaved brick according to any one of claims 5 to 9.
Citation Information
Patent Citations
Autoclaved flyash-lime brick and manufacturing method thereof
CN106278105A